Role of Image Guided FNAC in Assessment of Intra-Abdominal and Retroperitoneal Masses - Shrestha, Richa; Baidya, Pooja; Paudel, Nabin; Shrestha, Anil (Journal of Nepalgunj Medical College, 2023)
Introduction: Fine Needle Aspiration Cytology is a widely used method for palpable/nonpalpable masses. Radiological image guided Fine Needle Aspiration Cytology is less invasive, safe and cost effective method for diagnosis of masses in less accessible sites like intra-abdominal organs. Ultrasound or Computed Tomography guided methods are usually preferred. Aims: This study was done to evaluate the diagnostic utility of image guided Fine Needle Aspiration Cytology in an intra-abdominal and retroperitoneal lesions and confirmation by histopathology whenever available. Methods: This is a hospital based prospective study over a period of one year (October 2022 to September 2023) in department of Pathology, Nepalgunj Medical College, Kohalpur, Nepal. Patients who presented clinically and radiologically with intraabdominal or retroperitoneal masses were included in which direct Fine Needle Aspiration Cytology was not possible. A cytological opinion was made by correlating with clinical and radiological findings. Histological correlation was carried out in patients who went surgical excision or biopsy of lesion. Results: Among 52 cases studied, all were accessible via ultrasonography. Cytopathological diagnosis was obtained in 49 cases and three cases were unsatisfactory. Among them 44 were malignant, one was suspicious and seven were non-neoplastic. Liver was most frequently aspirated organ (23 cases) with commonest diagnosis being metastatic adenocarcinoma (17 cases). Cyto-histological correlation was available in 16 cases. This study shows 100% specificity and 93.3% sensitivity. Diagnostic accuracy was 94.2%. Conclusion: Image guided Fine Needle Aspiration Cytology plays an important role in diagnosis of deep-seated nonpalpable lesions. It is safe and provides rapid diagnosis with minimal complications.